2023
DOI: 10.1038/s41598-023-38087-9
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence of legacy effects of the 2018 drought on a mixed deciduous forest in Germany

Abstract: Forests play a major role in the global carbon cycle, and droughts have been shown to explain much of the interannual variability in the terrestrial carbon sink capacity. The quantification of drought legacy effects on ecosystem carbon fluxes is a challenging task, and research on the ecosystem scale remains sparse. In this study we investigate the delayed response of an extreme drought event on the carbon cycle in the mixed deciduous forest site ’Hohes Holz’ (DE-HoH) located in Central Germany, using the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 107 publications
(112 reference statements)
0
7
0
1
Order By: Relevance
“…We found strong declines in growth during the 2018-2020 drought event for the majority of the investigated tree communities (Figure 1). Other studies that assessed the impact of the 2018-2020 drought on forests have consistently reported signs of tree drought stress, reduced growth and increased tree mortality, both during and after the drought period (Buras et al, 2020;Obladen et al, 2021;Pohl et al, 2023;Schnabel et al, 2022;Schuldt et al, 2020;Senf et al, 2020). While our reported growth reduction by 36.8 % lines up with the finding of an earlier study by Thom et al, 2023, that reported a 41.3% reduction during the 2018-2020 drought, it should be kept in mind that our reductions are biologically even higher, because we expect an ontogenetic increase (Pretzsch, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found strong declines in growth during the 2018-2020 drought event for the majority of the investigated tree communities (Figure 1). Other studies that assessed the impact of the 2018-2020 drought on forests have consistently reported signs of tree drought stress, reduced growth and increased tree mortality, both during and after the drought period (Buras et al, 2020;Obladen et al, 2021;Pohl et al, 2023;Schnabel et al, 2022;Schuldt et al, 2020;Senf et al, 2020). While our reported growth reduction by 36.8 % lines up with the finding of an earlier study by Thom et al, 2023, that reported a 41.3% reduction during the 2018-2020 drought, it should be kept in mind that our reductions are biologically even higher, because we expect an ontogenetic increase (Pretzsch, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The growth responses of the tree communities at our site seemed to closely mirror the meteorological drought patterns, with the lowest growth rate in 2018, followed by 2019 and 2020. However, contrary findings from other studies point to 2019 as the year with the strongest growth reduction (Pohl et al, 2023;Salomón et al, 2022;Schnabel et al, 2022), attributed to the legacy effects of the 2018 drought (Anderegg et al, 2015;Kannenberg et al, 2020;Schnabel et al, 2022). Such drought legacies might be caused by diminished reserves of non-structural carbohydrates and altered carbon allocation, favouring the canopy and root system instead of radial stem growth (Hartmann & Trumbore, 2016;Brunner et al, 2015;Kannenberg et al, 2019).…”
Section: Strong Growth Reductions During Extreme Droughtmentioning
confidence: 94%
“…However, EcH 2 O-iso allows vegetation dynamics to be assessed (Douinot et al, 2019), and temporal changes in soil properties associated with land use change need to be incorporated (e.g., Poorter et al, 2021). In this regard, recent forest productivity changes associated with drought conditions could be used to better understand the complex lag effects of droughts on forests physiology and water cycling and incorporate this behaviour in models (e.g., Pohl et al, 2023).…”
Section: What Are the Implications For Water Storage And Age?mentioning
confidence: 99%
“…La sequía extrema como causa de deterioro del ecosistema tiene impactos positivos en el ciclo del carbono al comienzo de la temporada de vegetación, pero impactos negativos a finales del verano, mientras que los eventos de sequía a largo plazo tienen impactos generalmente negativos durante toda la temporada de crecimiento (Pohl et al, 2023).…”
Section: Sequía Extremaunclassified